The Emerald handbook of blockchain for business - Baker, H. Kent (Harold Kent), 1944-; Nikbakht, Ehsan; Stein Smith, Sean (Bingley, U.K. : Emerald Publishing Limited, 2021)
Although an emerging technology, blockchain is here to stay. Since its inception, imaginative thinkers have identified new ways for this powerful technology to bring innovative solutions to problems in the business world. Considered by many as an extreme and disruptive change, how can business leaders overcome resistance to the implementation of blockchain solutions and maximize its potential?'The Emerald Handbook of Blockchain for Business' equips academics, practitioners, and students with a broad understanding of the cutting-edge developments and applications of emerging blockchain technology. Covering the basic concepts while also showcasing practical applications in intricate real-world situations, this handbook bridges the gap between theory and practice, providing a useful balance of detailed and user-friendly coverage. Facilitating readers with a working knowledge of how blockchain functions and integrates within the business world, this handbook is essential reading for academics looking for a springboard for further research and practitioners needing a go-to resource for navigating the implementation of this fast-moving new technology.
Chapter 1. Blockchain: an overview / H. Kent Baker, Ehsan Nikbakht, and Sean Stein Smith -- Chapter 2. History of blockchain / Joseph'Joey' Ryan and Sean Stein Smith -- Chapter 3. Review of blockchain and emerging applications / Timothy Grief and Ehsan Nikbakht -- Chapter 4. Technical aspects of blockchain / Hak J. Kim -- Chapter 5. Public blockchains and applications / Hugo Benedetti -- Chapter 6. Private and hybrid blockchains and applications / Gina Pieters and Sean Stein Smith -- Chapter 7. Consensus mechanisms and related issues / Deniz Appelbaum -- Chapter 8. Token economies / Alim Khamisa -- Chapter 9. Proposed modifications to spur consumer adoption of blockchain / Katherine McKechnie, Alexandra M. Dunn, and Sayan Sarkar -- Chapter 10. Blockchain: speed, efficiency, decreased costs, and technical challenges / Amanda Wilkie and Sean Stein Smith -- Chapter 11. The importance of interoperability, decentralization, and choice / Kirk Phillips -- Chapter 12. Convergence with artificial intelligence and other related concepts / Lian Duan -- Chapter 13. Risk management and transference issues in blockchain technologies / Joseph Brunsman -- Chapter 14. Legal and regulatory issues in the temporary regime / J. Scott Colesanti -- Chapter 15. Regulatory ambiguity and its impact on blockchain / Shehan Chandrasekera -- Chapter 16. Considerations for blockchain adoption and integration / Michael Nizich and Michael Campisi -- Chapter 17. Blockchain applications in finance / Steven Cosares, Kristin Kalish, Thomas Maciura, and Andrew C. Spieler -- Chapter 18. Blockchain applications in healthcare / Alevtina Dubovitskaya -- Chapter 19. Blockchain applications in real estate / Joshua Harris and Ehsan Nikbakht -- Chapter 20. Blockchain applications in supply chain / Kaushik Sengupta -- Chapter 21. Crypto accounting valuation, reporting, and disclosure / Sean Stein Smith -- Chapter 22. Auditing and examining blockchain information / John'Jack' Castonguay.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Blockchains (Databases); Business enterprises; Computers, Blockchain; Business strategy